DIFFERENCES OF PLASMA INTERLEUKIN-6 AND TUMOR NECROSIS FACTOR-Î± LEVELS IN HEALTHY PEOPLE, RIFAMPICIN RESISTANT AND SENSITIVE PULMONARY TUBERCULOSIS PATIENTS - Wahyu Setiani Wibowo; Jusak Nugraha; Soedarsono Soedarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Increased tuberculosis in the world is caused by increased HIV-infected and antituberculous drugs (rifampicin) resistant individuals. IL-6 and TNF-Î± play an essential role in explaining the different degrees of inflammation in Rifampicin Resistant (RR) and Rifampicin Sensitive (RS) pulmonary tuberculosis patients, and healthy people. The research aimed to analyze the differences in plasma IL-6 and TNF-Î± levels in healthy people, Rifampicin Resistant (RR), and Rifampicin Sensitive (RS) pulmonary tuberculosis patients. A cross-sectional study was conducted from July-September 2017. Thirty-nine subjects were classified into RR pulmonary tuberculosis (n=15), RS pulmonary tuberculosis (n=12) based on GeneXpert examination and treated by antituberculous drugs â‰¤ 1 month, and healthy people (n=12) based on AFB results, Thorax X-ray, and tuberculin tests. IL-6 and TNF-Î± were done in all subjects using ELISA U-CyTech®(Biosciences, Inc.). Anova analyzed differences of IL-6 and TNF-Î± levels between groups. The mean IL-6 levels (pg/mL) in RR and RS pulmonary tuberculosis patients, and healthy people were 54.56±59.13, 27.05±37.04, 4.42±2.83, respectively. The mean TNF-Î± levels (pg/mL) in RR and RS pulmonary tuberculosis patients, and healthy people were 263.54±327.58, 250.25±314.20, 9.04±5.89, respectively. The mean differences between  IL-6 and TNF-Î± levels (pg/mL) between RR pulmonary tuberculosis patients and healthy people were 50.14±15.29 (p<0.05) and 254.59±8460 (p<0.05). Significant differences of mean IL-6 and TNF-Î± levels were found between RR pulmonary tuberculosis patients and healthy people.